The Influence of Utilitarian Value and Hedonical Values on Customer Loyalty through Customer Satisfaction - Sari, Ayuk Nurmalita; Ardiansari, Anindya (Universitas Negeri Semarang, 2019)
This study aims to determine the direct indirect influence of utilitarian value, hedonic value and customer satisfaction as an intervening variable on customer loyalty. The population of this research is customer of D’Bill Coffee & Resto. The number of sample is 107 respondents with purpose sampling technique through likert scale questionnaire. Data analysis using descriptive percentage and path analysis. The results show that utilitarian value affect customer loyalty, hedonic value affect customer loyalty and customer satisfaction influence customer loyalty and mediate the influence of utilitarian value and hedonic value on customer loyalty.